A new taxonomic treatment and comprehensive evaluation of the genus Aegokeras (Apiaceae) endemic to Turkey - Duran, Ahmet; Samigullin, Tahir; Lyskov, Dmitry (Phytotaxa, 2024)
The systematic position of the species Pimpinella ibradiensis, a narrow endemic to Turkey, was evaluated on the basis of morphological data and nrDNA ITS sequences. The species Pimpinella ibradiensis has been classified within the genus Pimpinella, particularly due to the similarity of leaf characteristics. However, the presence of trifoliolate leaves has been observed in both the isotype specimens and newly collected specimens from the field. Field observations, detailed morphological comparison, mericarp anatomy, and nrITS sequences data have supported the inclusion of this species within the genus Aegokeras. Furthermore, the description of the species P. ibradiensis has been emended, and the diagnostic morphological characters of all Aegokeras species are discussed. Additionally, the geographical distribution of the genus Aegokeras species is mapped, and an identification key with a description of all species is provided.